2001
DOI: 10.1093/protein/14.5.307
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of enzyme activity through three-phase partitioning: crystal structure of a modified serine proteinase at 1.5 Å resolution

Abstract: Three-phase partitioning is fast developing as a novel bioseparation strategy with a wide range of applications including enzyme stability and enhancement of its catalytic activity. Despite all this, the enzyme behaviour in this process still remains unknown. A serine proteinase, proteinase K, was subjected to three-phase partitioning (TPP). A 3 ml volume of proteinase K solution (3 mg/ml in 0.05 M acetate buffer, pH 6.0) was brought to 30% (w/v) ammonium sulphate saturation by addition of saturated ammonium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 23 publications
4
44
0
2
Order By: Relevance
“…However, unlike ammonium sulphate precipitation, this TPP often (though not always) results in subtle structural changes. This makes TPP valuable for wide range of applications such as protein purification, protein refolding and improving the catalytic efficiencies of the enzymes in both aqueous and non aqueous media [21][22][23][24][25][26][27][28][29][30][31]. The technique was introduced by Lovrein's group [21] who emphasized its importance in protein isolation and concentration [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike ammonium sulphate precipitation, this TPP often (though not always) results in subtle structural changes. This makes TPP valuable for wide range of applications such as protein purification, protein refolding and improving the catalytic efficiencies of the enzymes in both aqueous and non aqueous media [21][22][23][24][25][26][27][28][29][30][31]. The technique was introduced by Lovrein's group [21] who emphasized its importance in protein isolation and concentration [22].…”
Section: Introductionmentioning
confidence: 99%
“…The catalysis requires numerous conformational changes at various steps and higher rigidity or stability often comes out at the cost of catalytic efficiency. Earlier X-ray diffraction results with TPP treated Proteinase K had shown that the enzyme was considerably more flexible after this treatment [67].…”
Section: Three Phase Partitioning (Tpp) Of Enzymesmentioning
confidence: 91%
“…From the Table 1 it is obtained that recovery of enzyme was improved by this technique. Activity recovery of enzyme during the TPP increases due to structural changes and gains a high flexibility which can lead to higher catalytically activity [19,31,32]. Figure 4 shows that the optimum pH for potato invertase was detected at 4.5.…”
Section: Overall Purificationmentioning
confidence: 99%